'Got him': Revenge, emotions, and the killing of Osama bin Laden. Issue 1 (4th August 2016) - Cox, Lloyd; Wood, Steve
Abstract: The extrajudicial killing of Osama bin Laden (OBL) on 2 May 2011 was greeted with jubilation in the United States. The dominant interpretation of the event – expressed in US media, by US political elites, and on the streets of US cities – was that justice had been served on the perpetrator of the 9/11 atrocity and thereby a great historical wrong had been righted. This article argues that the 'justice' deployed was a proxy for revenge, understood as the infliction of harm on those who had inflicted harm on the avenger. The argument is situated in a broader discussion of the emotional topography on which acts of state revenge are politically premised. The bin Laden case is used to explore some issues raised by the growing literature on emotions in politics and International Relations including, most importantly, how emotions are collectivised and made public.